Analisis Tingkat Kesehatan Bank Dengan Menggunakan Metode CAMEL Pada PT Bank Muamalat Indonesia Tbk - Rafki Rachmat Akbar; Pandoyo (JURNAL ILMU ADMINISTRASI PUBLIK DAN BISNIS, 2020)
Writing in this paper, take the topic of the soundness analysis of Islamic banks. The methods used in conducting research that is by using the CAMEL. This research is compiled along with the rapid growth of Islamic banks lately. The development of Islamic banks is growing rapidly in recent years, prompting the authors to conduct research on the analysis of the soundness of the bank. The category is healthy, fairly healthy, less healthy, and unhealthy. This study authors do in PT Bank Muamalat Indonesia and the data used are the Financial Statements have been audited. CAMEL analysis has five factors, namely, the ratio of capital using the CAR (Capital Adequacy Ratio), asset factor using the ratio of earning assets (KAP), and the ratio of Allowance for Earning Assets Formed (PPAPYD) against Allowance for Earning Assets Mandatory Forms (PPAPWB ), management factors using the ratio of NPM (Net Profit Margin), factor income/profitability using ROA (Return on Assets) and ROA (Operating Expenses to Operating Income), and the aspect ratio of liquidity using FDR (Financing to Debt Ratio). Based on the results of the health of banks in PT Bank Muamalat Indonesia Tbk CAMEL values ​​obtained in 2010 was 87.35 HEALTH, HEALTHY in 2011 was 90.01, in 2012 89.66 is HEALTHY.